Biocompatibility enhancement via post-processing of microporous scaffolds made by optical 3D printer - Jeršovaitė, Jurga; Šarachovaitė, Ugnė; Matulaitienė, Ieva; Niaura, Gediminas; Baltriukienė, Daiva; Malinauskas, Mangirdas (Frontiers in Bioengineering and Biotechnology, 2023)
Providing a 3D environment that mimics the native extracellular matrix is becoming increasingly important for various applications such as cell function studies, regenerative medicine, and drug discovery. Among the most critical parameters to consider are the scaffold’s complicated micro-scale geometry and material properties. Therefore, stereolithography based on photopolymerization is an emerging technique because of its ability to selectively form volumetric structures from liquid resin through localized polymerization reactions. However, one of the most important parameters of the scaffold is biocompatibility, which depends not only on the material but also on the exposure conditions and post-processing, which is currently underestimated. To investigate this systematically, microporous scaffolds with pore sizes of 0.05 mm3 corresponding to a porosity of 16,4% were fabricated using the stereolithography printer Asiga PICO2 39 UV from the widely used resins FormLabs Clear and Flexible. The use of various polymers is usually limited for cells because, after wet chemical development, the non-negligible amount of remaining monomers intertwined in the photopolymerized structures is significantly toxic to cells. Therefore, the aim of this research was to find the best method to remove monomers from the 3D scaffold by additional UV exposure. For this purpose, a Soxhlet extractor was used for the first time, and the monomers were immersed in different alcohols. A Raman microspectroscopy was also used to investigate whether different post-processing methods affect DC (cross-linking) to find out if this specifically affects the biocompatibility of the scaffolds. Finally, mesenchymal stem cells from rat dental pulp were examined to confirm the increased biocompatibility of the scaffolds and their ability to support cell differentiation into bone tissue cells.